ANALISIS PENGARUH KEUNGGULAN PRODUK DAN KUALITAS PELAYANAN PADA KEPUASAN PELANGGAN TERHADAP MINAT MEREFERENSIKAN (Studi Pada Pelanggan Listrik Pra Bayar PT. PLN (Persero) APJ Semarang) 2008-2012 - Sari, Ratna Puspita; Khasanah, Imroatul (Faculty of Economics and Business Diponegoro University, 2015)
PT. PLN (Persero) is a service company in the field of employment-listrikan in Indonesia. The company is a state-owned entities (SOEs), which served to provide and distribute electrical energy to the community that contains a social mission with optimum service. The services company, has sought to improve the performance (performance) company optimally and efficiently, by increasing the ability to memahamui changes in market structure and is able to choose an effective marketing strategy through product excellence. This is done so that the PLN can give satisfaction to customers, so the reference interest could be better.The purpose of this research is to analyze the influence of product excellence and quality of service to customer satisfaction PLN (Persero) APJ Semarang, to analyze the effect of customer satisfaction on the reference interest PLN (Persero) APJ Semarang. The population in this study is the customer PT. PLN (Persero) APJ Semarang, with a total sample of 100 respondents. The sampling technique was accidental sampling. The data used are primary data and secondary data questionnaire with literature. The analysis tool used is multiple regression.The results of this study are: quality service and significant positive effect on customer satisfaction. Product excellence and significant positive effect on customer satisfaction. Customer satisfaction positive and significant effect on the interest reference.